Association Between Obstructive Sleep Apnea and Non-Alcoholic Fatty Liver Disease: Epidemiological Cross-Sectional Study and Mendelian Randomization Analysis - Yu T; Zhou Y; Wu X; Fang Z; Liu C (Nature and Science of Sleep)
Tianqi Yu,* Yongxu Zhou,* Xu Wu, Zhihao Fang, Chang Liu Department of General Surgery, Fourth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chang Liu, Email 600509@hrbmu.edu.cn Zhihao Fang, Email 202301635@hrbmu.edu.cnPurpose: Obstructive sleep apnea (OSA) is a common condition that is linked to various complications. Despite its prevalence, limited research has explored the association between OSA and non-alcoholic fatty liver disease (NAFLD). The aim of this study was to examine whether individuals at risk for OSA are more likely to develop NAFLD.Patients and Methods: This study employed a cross-sectional design coupled with Mendelian randomization, using data from the National Health and Nutrition Examination Survey (NHANES) collected between 2017 and 2020. A total of 6215 eligible participants were included. Multivariable logistic regression was performed to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for the relationship between OSA and NAFLD, adjusting for age, sex, ethnicity, education level, body mass index (BMI), diabetes, and hypertension. To assess causal inference and minimize observational bias, five distinct two-sample Mendelian randomization approaches were applied.Results: After excluding 9345 individuals who did not meet the study criteria, a total of 6215 participants were included. The weighted prevalence of OSA and NAFLD in the cohort was 43.1% and 43.0%, respectively. Compared with individuals without NAFLD, those with NAFLD were older (median age 52.0 vs 44.0 years), and exhibited higher levels of HbA1c (5.70% vs 5.40%), fasting glucose, total cholesterol, triglycerides, and liver enzymes such as ALT. Additionally, NAFLD patients had markedly higher rates of comorbid conditions including hypertension (65% vs 40%), diabetes (29% vs 14%), and OSA (51% vs 36%). After adjusting for potential confounders, multivariable logistic regression demonstrated a significant association between OSA and NAFLD (OR = 1.86, 95% CI: 1.63– 2.11, p < 0.001). Mendelian randomization analysis further suggested a potential causal effect of genetically predicted OSA on NAFLD risk (IVW OR = 1.066, 95% CI: 1.010– 1.125, p = 0.020).Conclusion: These findings suggest a potential association between OSA and the development of NAFLD. While the results provide preliminary evidence for a link, further longitudinal and interventional studies are needed to clarify causality and inform clinical practice.Keywords: obstructive sleep apnea, NAFLD, national health and nutrition examination survey, Mendelian randomization